Perbandingan Ukuran dan Komposisi Tubuh antara Mahasiswa Laki-Laki Atlet dan Non Atlet Universitas Padjadjaran: Comparison of Body Size and Composition between Male Student-Athletes and Non-Athletes at Universitas Padjadjaran - Mukti, Andhika; Nasihin, Shelvie Raffiza; Hanan, Hanifa; Rohmatullayaly, Eneng Nunuz (Departemen Biologi, Institut Pertanian Bogor, 2024)
Body composition is the relative proportion of fat and fat-free tissue in the body and indicates health profile. Athletes usually have a different body composition compared to the general population due to their involvement in intense sports activities. This research investigated the body size and composition among male student-athletes and non-athletes at Universitas Padjadjaran. The study used a cross-sectional method and anthropometric measurements on 14 athletes and 34 non-athletes. Anthropometric data consisted of height, weight, body fat, visceral fat, skeletal muscle, and Body Mass Index (BMI). Student-athletes have a lower average weight, body fat, and BMI than non-athletes. They tend to have body fat and visceral fat in the normal category (50% and 100%), whereas non-athletes (5.9% and 79.4%). Additionally, student-athletes have more skeletal muscle (63.4%) than non-athletes (47.1%). Furthermore, nutritional status based on BMI values indicates that student-athletes tend to fall within the normal category at 78.8%, while non-athletes are only at 44%. These results demonstrate that the body size and composition of student-athletes reflect better physical fitness, resulting in a better nutritional status than non-athletes at Universitas Padjadjaran.